The Potency of Maillard Conjugates Containing Whey Protein as Natural Emulsifier - Iceu Agustinisari; Kamarza Mulia; Niken Harimurti; Mohammad Nasikin; null Rienoviar; Heny Herawati; Lamhot Parulian Manalu (International Journal of Food Science)
There is a continued need for the advancement of natural emulsifiers to replace synthetic emulsifiers, driven by human health concerns. This study is aimed at producing protein-polysaccharide conjugates through the Maillard reaction and at evaluating its ability as an emulsifier based on its emulsifying properties. The proteins used in this study were bovine milk whey protein and soy protein isolates, while the polysaccharides were maltodextrin and pectin. The protein-polysaccharide conjugation used a Maillard reaction under dry heating conditions. The protein and polysaccharide mass ratios were 1 : 2 and 1 : 3. The results showed that the types of proteins and polysaccharides and their mass affect the surface tension of the conjugate products. Whey protein-pectin conjugates with a mass ratio of 1 : 2 and a concentration of 1% had the lowest surface tension at 43.77 dyne/cm2. This conjugate sample also showed the highest emulsifying index at 27.20 m2/g. The conjugate powder containing pectin as a polysaccharide showed better emulsifying activity than that of those containing maltodextrin. However, the smallest droplet size of the emulsion (256.5 nm) resulted from the emulsification process using whey protein-maltodextrin conjugates as an emulsifier. The FTIR and gel electrophoresis (SDS-PAGE) analysis confirmed the conjugation formation. In general, protein-polysaccharide conjugates containing whey protein could potentially act as a natural emulsifier for food.